Crush Syndrome Patient Care in Intensive Care Unit - Kelez Yayik, Aycan (Cerrahpaşa Medical Journal, 2023)
Crush syndrome is a systemic picture that develops as a result of prolonged compression, immobilization, and crushing of muscle groups after trauma and collapse. It affects numerous physiological systems and lays the groundwork for surgical and medical issues. After direct trauma, crush syndrome is the second most common cause of death in large-scale disasters like earthquakes. Rhabdomyolysis, which develops with loss of perfusion owing to compression of the limb muscles, is the primary initiator of crush syndrome.Rhabdomyolysis has a systemic effect whereby intracellular products including electrolytes, enzymes, and myoglobin rise quickly in the bloodstream and result in potentially fatal acute kidney injury and electrolyte imbalances. The 2 main factors that contribute to this syndrome’s mortality are hyperkalemia and acute tubular necrosis. Infections, compartment syndrome, hemorrhage, hypovolemic shock, heart failure, respiratory failure, and other problems are also brought on by it. The management of electrolyte imbalances and associated arrhythmias, the successful treatment of compartment syndrome, the avoidance of infections, and the prevention of potential consequences are all important tasks for intensive care nurses. The administration of the care and treatment process for a trauma patient admitted to intensive care depends heavily on the knowledge, abilities, and experience of nurses Cite this article as: Kelez Yayik A. Crush syndrome patient care in intensive care unit. Cerrahpaşa Med J 2023;47(S1):33-37.